Current Regulation and Initial Considerations for Successful Development and Commercialization of Microbiome Therapies - Thanush, D.; Basavaraj, H. C.; Gowrav, M. P. (Advanced Gut & Microbiome Research, 2023)
The gut microbiome is frequently referred to as the “second brain” or “second genome,” referring to the impact of the gut microbiota on our health. The microbiome is formed at birth, grows with the host, and is impacted by environmental variables such as nutrition, antibiotics, and lifestyle. Understanding the host health-gut microbiota correlation opens the possibility of modifying the gut microbiome to manage an individual’s health. Several techniques, such as probiotic, prebiotic, synbiotic, and faecal microbiota transplantation (FMT), are explored to alleviate the dysbiosis-related negative consequences and restore the gut microbiota in humans. While microbiome-based medicines have made remarkable progress in the last decade, from prebiotics and probiotics to live biotherapeutics, there are still safety concerns and regulatory issues to be addressed. The FMT treatment is currently experimental and lacks authorization, posing numerous ethical, legal, and social challenges that must be resolved as part of an effective regulatory policy response. This study gives an outline of our current understanding of microbiome restoration approaches as well as safety concerns regarding how these approaches are regulated. It presents an outline of the contemporary gut microbiome therapeutic development landscape and an assessment of the commercialization hurdles encountered.